2017
DOI: 10.1007/s11854-017-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Small-time sharp bounds for kernels of convolution semigroups

Abstract: We study small time bounds for transition densities of convolution semigroups corresponding to pure jump Lévy processes in R d , d ≥ 1, including those with jumping kernels exponentially and subexponentially localized at infinity. For a large class of Lévy measures, non-necessarily symmetric nor absolutely continuous with respect to the Lebesgue measure, we find the optimal, both in time and space, upper bound for the corresponding transition kernels at infinity. In case of Lévy measures that are symmetric and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 51 publications
6
68
0
Order By: Relevance
“…For some classes of Lévy processes (e.g. relativistic stable and tempered stable) it can be shown that the density has exponential decay exp(− | |), see the exact heat kernel estimates obtained by Kaleta & Sztonyk [24,25].…”
Section: Exists Is Infinitely Often Differentiable and Satisfies Thementioning
confidence: 86%
See 1 more Smart Citation
“…For some classes of Lévy processes (e.g. relativistic stable and tempered stable) it can be shown that the density has exponential decay exp(− | |), see the exact heat kernel estimates obtained by Kaleta & Sztonyk [24,25].…”
Section: Exists Is Infinitely Often Differentiable and Satisfies Thementioning
confidence: 86%
“…For some classes of Lévy processes (e.g. relativistic stable and tempered stable) it can be shown that the density has exponential decay exp(m|x|), see the exact heat kernel estimates obtained by Kaleta & Sztonyk . (iii)Let ψ be a continuous negative definite function with Lévy triplet (b,0,ν). If ψ satisfies the sector condition, then it is possible to give sufficient conditions in terms of fractional moments of νfalse|Bfalse(0,1false) and νfalse|Bfalse(0,1false)c which ensure that ψ satisfies the growth condition for real z , cf.…”
Section: Heat Kernel Estimates For Lévy Processesmentioning
confidence: 99%
“…In the proofs below we will often use the fact that (4.9) and (3.25) imply lim inf |ξ |→∞ ψ(ξ )/ log |ξ | > 0, which guarantees that assumption (A2) holds. Indeed, observe that by [36,Lem. 5 (a)], (2.4) and (4.8),…”
Section: Specific Casesmentioning
confidence: 98%
“…The convolution condition (A1.3) has been introduced in [33] and proved to be a strong tool in studying large-scale properties of jump Lévy processes. Recently, in [36] it was also used to characterize the short-time behaviour of heat kernels for a large class of convolution semigroups. It can be easily checked that (A1.3) in fact implies (A1.2), see [36, Lem.…”
Section: Definition 21 (Symmetric Jump-paring Lévy Processes)mentioning
confidence: 99%
See 1 more Smart Citation